Analysis of blood calcium levels in calcium water consumers - Rubak, Bonni; Umar, Ani; Reymon, Reymon; Jannah, Nanda Reski (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Water is a primary and basic human need. One of the chemical parameters that must be met for drinking water needs is mineral content, such as calcium and magnesium. Water hardness is a condition in which there is excessive calcium and magnesium content, which is commonly known as calcareous water. If consumed long-term, high-water hardness that exceeds normal limits can interfere with body health. Specifically, excess calcium in the body can cause hypercalcemia, hyperparathyroidism, kidney stones, and muscle tissue damage (muscle weakness). Objective: This study aims to determine blood calcium levels in individuals who consume calcareous healthy water. Methods: The type of research used is descriptive-analytical, with blood calcium level analysis carried out using the Ion Selective Electrode (ISE) method through the Electrolyte Analyzer (CBS400). Result: Based on the results of the study, it was obtained that blood calcium levels in 30 community respondents in Ranomeeto District (100%) were above the reference value, indicating high blood calcium levels. Conclusion: blood calcium levels in people who consume lime juice indicate high blood calcium levels. Consuming water with a high lime content can hurt health. Therefore, people need to consider the quality of the drinking water they drink, especially those that have a high lime content, to maintain heart and kidney health in the long term.